Leitura literária em discurso : a escolarização da literatura no ensino fundamental II - Cenedezi, Marineia Lima (2015)
In this research we propose reflections related to working with reading practices of literary texts recommended by the State of São Paulo Curriculum. From an interpretive view through the perspective of the Discourse Analysis, we have observed the main teaching tools proposed by the São Paulo State Education Department, called Teacher Guidelines and Student Guideline. These tools are intended for students of the eighth grade of schools that belong to the São Paulo state public education, with the purpose of outlining the possible obstacles that obstruct the literary reading practices and prevent the students literary literacy. The justification for our research lies on the belief that the literary reading activities guided by these instruments have been co-responsible for the hindered literary reading skills within those schools. The theoretical-methodological reflections conducted by the Discourse Analysis, Literacy Theory, and Theory of Aesthetic Effect have provided theoretical basis for an investigation of methodological misrepresentations brought by the instruments used for the creation of literary readers. We observed that the discourse conveyed in the analyzed material derives from the school ideology. There is a contradiction between what is written in the Guidelines and what effectively occurs. Its explicit purpose is that the literary text should be the object not only of analysis and interpretation, but also of social practice in order to restore the pleasure dimension of literature, which is regarded as essential for the autonomous reader and, therefore, should be approached throughout the school year. However, the recommended practice (teaching step-by-step) contradicts the expressed purpose: the activities of the Guidelines related to literary reading are subverted to serve another purpose of cognitive or informational order, shattering the pleasure dimension of literature. The \"learning situations\" in the Guidelines promote literary reading situations that silence subjects/students, preventing their expression, due to questionings that require standard answers and domesticated interpretations. In our view, this constitutes a major limitation of the pedagogical recommendations presented by the São Paulo State Education Department for literature teaching. In order to overcome this limitation, we have complemented our study with a proposal of didactic intervention for the teaching of literary reading, implemented in accordance with the theoretical framework of Literacy and the Theory of Aesthetic Effect, which focus on the interaction between reader and text, emphasizing the active role of the reader in the construction of meaning in a literary text.